Digital innovation and manufacturing employment - based on the analysis of mediating and threshold effects - JianJiang Liu; Qi Tang; Fidelis Ayangbah (Cogent Economics & Finance, 2024)
Profound changesunseen in a century' superimpose the complex background of weak global economic growth. Employment affects a country's economic development and social stability, and is an urgent issue that every country needs to solve. This study examines the impact of digital innovation on the absorption capacity of manufacturing jobs, using data from listed companies from 2011 to 2021. The mechanism test indicates that digital innovation fosters enterprise employment through three principal avenues: enhanced total factor productivity, alleviation of enterprise financing constraints, and expansion of the market size. A heterogeneity analysis indicates that the impact of digital innovation is more pronounced in low-technology firms, state-owned firms, and technology-intensive firms. Further analysis revealed that the level of enterprise digital innovation positively affects the employment of high-tech and medium-skilled labour, while having no significant impact on low-skilled labour. In addition, the impact of digital innovation on employment in manufacturing enterprises is not a simple linear relationship, but there is a double threshold effect. When the level of digital innovation reaches a certain threshold, the effect of promoting employment becomes more significant. This study enriches the literature on the impact of digital innovation on employment and provides a useful reference for local governments on how to alleviate employment pressures. The paper draws on data from listed companies in China to examine the impact of digital innovation on employment in the manufacturing industry. It combines theoretical insights with empirical evidence, employing the two-way fixed-effect model and the threshold effect model to investigate this relationship. The paper contributes to the theoretical understanding of the impact of digital innovation on employment and has significant practical implications, offering a valuable reference point for policymakers seeking to address employment challenges.
Keywords: 330; Digital innovation; stable employment in manufacturing; technological progress; threshold effects